Dual-task interference effects on cross-modal numerical order and sound intensity judgments: the more the louder? - Alards-Tomalin, Doug; Walker, Alexander C.; Nepon, Hillary; Leboe-McGowan, Launa C. (Quarterly Journal of Experimental Psychology, 2017)
In the current study, cross-task interactions between number order and sound intensity judgments were assessed using a dual-task paradigm. Participants first categorized numerical sequences composed of Arabic digits as either ordered (ascending, descending) or non-ordered. Following each number sequence, participants then had to judge the intensity level of a target sound. Experiment 1 emphasized processing the two tasks independently (serialprocessing), while Experiments 2 and 3 emphasized processing the two tasks simultaneously (parallelprocessing). Cross-task interference occurred only when the task required parallel processing and was specific to ascending numerical sequences, which led to a higher proportion ofloudersound intensity judgments. In Experiment 4 we examined whether this unidirectional interaction was the result of participants misattributing enhanced processing fluency experienced on ascending sequences as indicating a louder target sound. The unidirectional finding could not be entirely attributed to misattributed processing fluency, and may also be connected to experientially derived conceptual associations between ascending number sequences and greater magnitude, consistent with conceptual mapping theory.